Bee venom phonophoresis on mild to moderate localized plaque psoriasis on a knee joint: a randomized controlled trial - Heba M. Elfeky; Ahmed М. Elfahl; Maha G. Ibrahim (Вестник восстановительной медицины)
Introduction. In psoriasis, plaque psoriasis is the most common kind. Patients may experience mild to severe symptoms, and while the sickness is not lethal, it is difficult to cure.